Virtual reality technology to enhance speaking, cultural understanding and overall learning experiences among efl teenage learners - Carrera Lara, Daniel Eduardo (2023)
Virtual reality (VR) technology offers an immersive and interactive medium that can revolutionize language learning experiences, particularly for EFL teenage learners. This study explores the potential of VR to enhance speaking skills, cultural understanding, and overall learning engagement among this demographic. VR allows learners to practice conversational English in simulated real-world contexts by recreating authentic environments and scenarios. The multi-sensory nature of VR and gamification elements can make language practice more engaging and memorable. Additionally, VR experiences can expose learners to diverse cultural settings, fostering cross-cultural awareness and appreciation. This study used mixed-methods research employing both quantitative and qualitative data collection methods—pre- and post-intervention classes measured improvements in speaking proficiency and cultural knowledge. Furthermore, surveys, interviews, and observational data provided insights into learners' perceptions, motivation levels, and overall learning experiences. The findings indicate that incorporating VR activities significantly improved participants' speaking fluency, vocabulary use, and comprehension. Moreover, learners demonstrated heightened cultural sensitivity and understanding after engaging with immersive cultural simulations. Notably, the interactive and gamified nature of VR learning environments enhanced learners' motivation, engagement, and enjoyment of the learning process. This study highlights the promising potential of VR technology in transforming language education, particularly for teenage EFL learners. By providing immersive, contextualized, and interactive learning experiences, VR can foster skill development, cultural competence, and overall learner motivation, paving the way for more effective and enjoyable language acquisition.